Motivaciones epistemológicas sobre las que se basan las elecciones didácticas llevadas a cabo en las actividades educativas en Italia, desde pre-escolar hasta el bienio superior - D'Amore, B. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This article offers a general view of the recent curricular changes of Mathematics in Italy and discusses the epistemological conceptions underlying the different didactical choices now available or appearing along with curricular changes.